If-then planning. Issue 1 (2nd January 2021) - Bieleke, Maik; Keller, Lucas; Gollwitzer, Peter M.
ABSTRACT: The self-regulation strategy of forming implementation intentions has now been studied for almost 30 years. We trace the development of this research and explicate the questions that have been addressed. We then present current research that investigates the consequences of implementation intentions for flexible goal striving, behaviour in situations for which one had not planned, and neuropsychological processes underlying the action control by implementation intentions. Next, we turn to novel applications focusing on how implementation intentions affect physical endurance and promote strategic information processing. Our review concludes with an outlook on future research on implementation intentions that covers emerging individual difference perspectives, innovative approaches to characterize underlying cognitive processes, and the prospects of integrating insights from related fields of research. As such, our review is an empathic call for addressing the many intriguing conceptual and empirical questions that still revolve around implementation intentions.